A comparative study on the efficacy and safety of biosimilar (Rimmyrah) and reference ranibizumab in patients with diabetic macular edema - Zhai, Gaixia; Ren, Xiaona; Xu, Bing; Mi, Dongming (Frontiers in Pharmacology, 2026)
ObjectiveThis study evaluated the efficacy and safety of the biosimilar Rimmyrah versus the reference ranibizumab in patients with diabetic macular edema (DME).MethodsThis retrospective study included 70 patients with DME. They were divided into two groups: 35 patients (35 eyes) received the reference ranibizumab, and 35 patients (35 eyes) received the biosimilar ranibizumab. All patients were treated following a 3+ pro re nata (PRN) regimen. Best-corrected visual acuity (BCVA) and central retinal thickness (CRT) were compared between the groups at 3, 6, and 12 months post-treatment. Additionally, the foveal avascular zone (FAZ) area and macular vessel density were compared at baseline and 12 months, along with the total number of intravitreal injections required.ResultsThere were no statistically significant differences between the two groups in BCVA or CRT at any time point (all P > 0.05). Consistent with the therapeutic effect of ranibizumab, both groups showed significant improvements from baseline in BCVA and CRT (all P < 0.05). Similarly, no intergroup differences were found in FAZ area, superficial vascular density (SVD), or deep vascular density (DVD) at baseline or 12 months (all P > 0.05), with both groups exhibiting significant within-group improvements post-treatment (reduced FAZ, increased SVD and DVD; all P < 0.05). No statistically significant difference was observed in the mean number of intravitreal injections between the reference ranibizumab group (3.43 ± 0.65) and its biosimilar group (3.69 ± 0.76) during the study period (P = 0.1530). No treatment-related serious ocular or systemic adverse events occurred in either group during the 12-month follow-up.ConclusionThe ranibizumab biosimilar (Rimmyrah) showed similar safety and efficacy profiles to its reference product in the treatment of diabetic macular edema.